Integration of geophysical surveys, ground hyperspectral measurements, aerial and satellite imagery for archaeological prospection of prehistoric sites: The case study of Vészto{doubleacute}-Mágor Tell, Hungary - Sarris, Apostolos; Papadopoulos, Nikos G.; Agapiou, Athos; Salvi, Maria Cristina; Hadjimitsis, Diofantos G.; Parkinson, William A.; Yerkes, Richard W.; Gyucha, Attila; Duffy, Paul R. (My University, 2013)
An integration of geophysical surveys, ground hyperspectral data, aerial photographs and high resolution satellite imagery for supporting archaeological investigations at the multi-component Vészto{doubleacute}-Mágor Tell, located in the southeastern Great Hungarian Plain, is presented in this study. This is one of the first times that all these techniques have been combined and evaluated for retrieving archaeological information. Geophysical explorations, specifically magnetic gradiometry and ground penetrating radar methods, have revealed shallow linear anomalies and curvilinear rings at the Tell. The use of remote sensing images has confirmed the diverse anomalies with respect to geophysics through photointerpretation, radiometric and spatial enhancements. Moreover, several indices from ground hyperspectral data also have revealed stress vegetation anomalies. These integrated results were used to map the main areas of archaeological interest at the Vészto{doubleacute}-Mágor Tell and plan future excavations. It was found that these multiscalar data can be used efficiently for detecting buried archaeological features.
Keywords: Archaeological prospection; Spectroradiometric measurements; Geophysical surveys; Satellite and aerial images; Remote sensing archaeology